KS01.4.A NK cells as key orchestrators in mediating the anti-tumour response to immune checkpoint blockade in melanoma brain metastases. (9th September 2021) - Fife, C M; Williams, J; Brownlie, R; Andreou, T; Sunderland, A; McKimmie, C; Salmond, R; Lorger, M
Abstract: BACKGROUND: Brain metastases (BrM) are an unmet clinical need with poor prognosis. 60% of melanoma patients develop BrM. BrM are strongly understudied due to frequent exclusion from clinical trials, and hence treatment options commonly lag behind. Antibodies targeting the immune-inhibitory receptors cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) have demonstrated efficacy against melanoma BrM. Despite this, therapeutic responses are highly variable, and it is unknown why therapy fails in a high proportion of patients. Improved therapeutic strategies require a thorough understanding of potentially exploitable mechanisms of therapeutic efficacy. Our data previously implicated different immune cells, foremost CD8+ T cells, but also NK cells, in the intracranial efficacy and enhanced survival benefit of immune checkpoint blockade (ICB). Our aim here is to investigate the role of NK cells in mediating the response to ICB in melanoma BrM. MATERIAL AND METHODS: To study the role of NK cells in the response to ICB in melanoma BrM, a tumour transplantation model of B16 melanoma with simultaneous extracranial (i.e., flank) and brain tumours in C57BL/6 mice was utilised. NK cells were depleted through administration of anti-asialo-GM1 NK cell-depleting antibodies. Confirmation of NK cell depletion and quantification of intratumoral immune cell populations was performed using flow cytometry. Intratumoral gene expression of key chemokines and immune mediator genes was assessed using RT-qPCR and mRNA-seq. RESULTS: Highly variable response to ICB with respect to intratumoral accumulation of CD8+ T cells allowed separation of mice into responders and non-responders and revealed genes and pathways associated with response to ICB. NK cell depletion reversed the ICB-mediated increase in the accumulation of CD8+ T cells and significantly reduced the expression of genes associated with response in intracranial and extracranial tumours. The ICB-mediated significant increase in gene expression of various chemokines (i.e., Cxcl9/10) and immune mediators (i.e., Ifng, Prf1 and Gzmb) was significantly abrogated upon NK cell depletion. CONCLUSION: NK cells play a critical role in the underlying mechanisms of ICB efficacy through their modulation of the tumour microenvironment and enhancement of CD8+ T cell accumulation in intracranial tumours. Targeting of NK cells may allow potentiation of ICB therapy in the brain, as well as at extracranial sites.